Producer gas conditioning from a rice husk gasifier for engine application - Jain, A K; Panesar, B S (Journal of Agricultural Engineering, 2005)
The producer gas generated from an open core throatless down draft gasifier even after passing through a gas conditioning unit comprising of a water scrubber, dry filter, a cyclone separator and a fabric filter, contains about 200 mg/NmÂ³ of tar. This was specially the case during rainy season i.e periods of high relative humidity and temperature. The tar after condensing stick to the engine valves and connecting pipe lines causing problems in smooth operation of the engine. The tar content in the gas is a function of gas residence time in the dry scrubber once the gas is cooled to ambient temperature in water scrubber. A series of experiments were conducted to study the effect of gas residence time and the superficial gas velocity in the dry scrubber on tar reduction in producer gas keeping the water scrubber and fabric filter as such. With a gas residence time of 12-15 seconds and superficial gas velocity of 0.03 m/s in dry filter the tar content can be brought down to around 50 mg/NmÂ³ .